Pengaruh Ukuran Perusahaan, Pertumbuhan Perusahaan, dan Opini Audit Tahun Sebelumnya Terhadap Opini Audit Going Concern - Anatasia Yuana Widyastuti; Desi Efrianti (Institut Bisnis dan Informatika Kesatuan, 2021)
The company was established with the goal of ensuring its continuation (going concern). The auditor is supposed to provide an early warning to the company in the form of a going concern audit opinion when the company's financial condition is in jeopardy. If an entity encounters varied conditions with the assumption of going concern, a going concern audit opinion is one of the audit opinions offered to its financial statements. Many assumptions are made while evaluating a company's going concern status; consequently, variables are required as a solid benchmark for determining a company's going concern status. This study aims to (1) determine whether the size of the company has a significant effect on going concern audit opinion (2) To find out whether company growth has a significant effect on going concern audit opinion (3) Determine if the prior year's audit opinion has a significant impact on the current year's audit opinion. (4) Determine whether the company size, company growth, and the prior year's audit opinion have a significant impact on going concern audit opinion. This research is in the form of quantitative descriptive research. The sample used in this study was selected using a purposive sampling method, with a sample of 81 data from 27 companies that met the criteria. The data analysis method used is logistic regression analysis. The research data was processed using SPSS software. Based on the research, it can be concluded that (1) company size has no significant effect on going concern audit opinion with a significance value of 0.321 and a regression coefficient value of -0.568, meaning that the larger of the company size, the smaller probability of getting a going concern audit opinion (2) Company growth has no significant effect on going concern audit opinion with a significance value of 0.963 and a regression coefficient value of 0.027, meaning that the higher the company's growth ratio, the greater the probability of getting a going concern audit opinion (3) The prior year's audit opinion has a significant positive effect on going concern audit opinion with a significance value of 0.000 and a regression coefficient value of 6.885, meaning that companies that received a going-concern audit opinion in the previous year will have a higher probability of getting a going-concern audit opinion (4) Company size, company growth and prior year's audit opinion simultaneously have a significant effect on going concern audit opinions on manufacturing companies listed on the Indonesia Stock Exchange in 2017-2019. Keywords: Company Size, Company Growth, Prior Year’s Audit Opinion, Going Concern Audit Opinion